Abundant and Rare Bacterial Taxa Structuring Differently in Sediment and Water in Thermokarst Lakes in the Yellow River Source Area, Qinghai-Tibet Plateau - Ren, Ze; Zhang, Cheng; Li, Xia; Ma, Kang; Cui, Baoshan (Frontiers in Microbiology, 2022)
Thermokarst lakes are forming from permafrost thaw and are severely affected by accelerating climate change. Sediment and water in these lakes are distinct habitats but closely connected. However, our understanding of the differences and linkages between sediment and water in thermokarst lakes remains largely unknown, especially from the perspective of community assembly mechanisms. Here, we examined bacterial communities in sediment and water in thermokarst lakes in the Yellow River Source area, Qinghai-Tibet Plateau. Bacterial taxa were divided into abundant and rare according to their relative abundance, and the Sorensen dissimilarity (βsor) was partitioned into turnover (βturn) and nestedness (βnest). The whole bacterial communities as well as the abundant and rare subcommunities differed substantially between sediment and water, in terms of taxonomical composition, α-diversity, and β-diversity. Sediment had significantly lower α-diversity indexes but higher β-diversity than water. In general, bacterial communities are predominantly governed by strong turnover processes (βturn/βsor ratio of 0.925). Bacterial communities in sediment had a significantly higher βturn/βsor ratio than in water. Abundant subcommunities were significantly lower in βturn/βsor ratio compared to rare subcommunities. The results suggest that the bacterial communities of thermokarst lakes, especially rare subcommunities or particularly in sediment, might be strongly structured by heterogeneity in the source material, environmental filtering, and geographical isolation, leading to compositionally distinct communities. This integral study increased our current knowledge of thermokarst lakes, enhancing our understanding of the community assembly rules and ecosystem structures and processes of these rapidly changing and vulnerable ecosystems.